Fast processing and continuous simulation of automotive structural composite components - Henning, Frank; Kärger, Luise; Dörr, Dominik; Schirmaier, Fabian J.; Seuffert, Julian; Bernath, Alexander (Composites science and technology, 2019)
Due to application-specific tailoring, continuous fiber reinforced plastics (CoFRP) provide an exceptional lightweight potential and are particularly suited for structural components. The use of CoFRP specifically for weight reduction of the automotive car body is the major focus of this feature article. Automotive mass production requires fast and qualified, thus highly automated and material efficient manufacturing technologies. Consequently, CoFRP manufacturing for automotive differs considerably from conventional CoFRP manufacturing for aerospace, particularly in terms of higher throughput with higher investment, but lower operating effort. Furthermore, automotive structures have smaller dimensions with more complex shapes, which makes it more challenging to avoid forming defects and to ensure complete injection. Since manufacturing makes the main difference between automotive and aerospace composite components, this feature article puts emphasis on the process technologies and on the corresponding material behavior and process simulation methods. For a holistic product design of automotive CoFRP components, a simultaneous virtual description and virtual optimization of both manufacturing process and structural capacity is necessary. Production effects must be considered in the part design and, thus, must be reliably predicted by process simulation as well as taken into account in subsequent simulation steps. This feature article therefore evaluates the current state of the art in the continuous virtual representation of CoFRP process chains, including the process steps forming, injection and curing. Furthermore, the integrated optimization along this CAE chain is a key factor for an economic part design and therefore another major subject of this article.